- #1

silvermane

Gold Member

- 117

- 0

## Homework Statement

Show that for all integers n,m where 0 ≤ m ≤ n

The sum from k=m to n of {(nCk)*(kCm)} = (nCm)*2^(n-m)

## The Attempt at a Solution

So for the proof, I have to use a real example, such as choosing committees, binary sequences, giving fruit to kids, etc. I have been thinking hard on it, but I don't fully understand it to do so. Any hints would be wonderful. I don't exactly want the answer, just an understanding! Thank you for your time :)